Carl Schmitt, Mao Zedong and the Politics of Transition - Zheng, Qi. author. aut Link
VII, 177 p.
Keywords: This book develops a new way of reading and benefiting from Schmitt's legal and political theories. It explores Schmitt's theories from the perspective of what I refer to as the politics of transition. It also contributes to identifying the real theoretical relationship between Schmitt and Mao.